Classical and Neoclassical Elements in Industrial Organization - Mark Glick; Eduardo Ochoa (Levy Economics Institute of Bard College, 1988)
This article analyzes the theoretical foundations of industrial organization studies of monopolistic and competitive pricing. Our analysis will focus on the central debates of the 1950s, 1960s, and 1970s which formed the theoretical basis of the modern industrial organization paradigm. We will argue that despite claims to the contrary, and often unknowingly, the majority of these studies adopted a mixture of both classical and neoclassical elements . 2 We will try to show that the lack of a firm theoretical grounding has led to three types of confusion in this literature. First, there is a lack of clarity concerning what measure of profitability should be equalized in competitive equilibrium. A debate has developed concerning whether the rate of profit, total profit, or the profit margin, is the appropriate variable to study. Second, the industrial organization approach to monopoly and competition has never adequately resolved over what period of time profit-rate differentials must be studied. In this regard, Yale Brozen's criticism of the short-run nature of early profit rate-market structure studies is discussed. Third, we will argue that from a classical point of view, firm studies of profitability which draw conclusions for industry phenomena have been misguided. Harold Demsetz' work on concentration and efficiency will be referred to as an illustration. We will conclude by questioning the practicability of a purely neoclassical grounding for industrial economists, since they have been impelled to abandon this approach in their investigation of reality.
Keywords: 330